PENINGKATAN HASIL BELAJAR PPKn MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI SISWA KELAS IV SD NEGERI 011 BERINGIN MAKMUR KECAMATAN KERUMUTAN - Ambari ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
SD Negeri 011 Beringin Makmur, especially in the fourth grade, KKM to subjects who have ditatapkan PPKn is by KKM is 65. Particularly in the fourth grade SD Negeri 011 Beringin Makmur PPKn low student learning outcomes. It can be seen from the students after the test in midterm average value of only 61.5. Based on the preliminary study authors, the low student learning outcomes PPKn caused by several things, the strategies used in teaching the teacher does not comply with the demands of learning and students during lessons PPKn frequency only ask very little because the material is only presented in the form of lectures. The purpose of this study is to improve learning outcomes in subjects PPKn through the implementation of inquiry learning model SD Negeri 011 Beringin Makmur fourth grade students. This research is a classroom action through the stages of planning, implementing action, observation and reflection. Design research is the model cycle of improvement planning, implementing action, observation and reflection. The subjects were students in grade IV SD Negeri 011 Beringin Makmur with the number of 30 people, including 15 women and 15 men. While the object of the research is PPKn student learning outcomes, the data used in this study focuses on learning outcomes data PPKn only. From the results of the action, can be seen learning outcome Civics students from before action is taken (preliminary data) cycle I and after the action on the second cycle by improving student learning outcomes that have been achieved, known completeness class on preliminary data only 15 or (50 %) of all students and after repair in the first cycle has increased to 26 people or 87% of the total class IV student SD Negeri 011 Beringin Makmur. After the improvement in cycle II to be increased to 27 students or 90%.